Nanofluid flow past a static wedge with velocity slip condition / Intan Nursabrina Saharin, Noraihan Afiqah Rawi and Mohamad Hidayad Ahmad Kamal - Saharin, Intan Nursabrina; Afiqah Rawi, Noraihan; Ahmad Kamal, Mohamad Hidayad (Universiti Teknologi MARA, Perak, 2023)
Nanofluids are known for their exceptional thermophysical properties, especially their thermal conductivity, which make them ideal for a number of heat transfer applications. In this study, the mixed convection nanofluid flow past a static wedge with the presence of velocity slip condition is investigated. The problem is governed by a system of partial differential equations which then transformed into a set of nonlinear ordinary differential equations by using an appropriate similarity transformation. The transformed governing equations are then solved numerically by using MATLAB bvp4c solver. Numerical solutions obtained are presented graphically in the form of velocity and temperature profiles for different values of nanoparticles volume fraction, wedge angle and velocity slip. It is found that the increasing values of the wedge angle parameter causes the velocity of the fluid to increase whereas the temperature profile of the nanofluid decreases, additionally it observed that velocity of the fluid increase when velocity slip is increased. The findings of this study provide valuable insights into optimizing heat transfer processes in various engineering applications by leveraging the enhanced thermal properties of nanofluids and considering factors such as wedge angle and velocity slip.